Improving Students’ Reading Comprehension of Narrative Text Through Storytelling Using Webtoon at First Grade of MA Daruttolibin Watumalang (Lembaga Pengembangan Kinerja Dosen, 2026)
English is an international language that plays a vital role in education and technology; therefore, students are required to master reading comprehension skills, especially narrative texts, to face the challenges of globalization. This study, entitled